Transseptal mitral valve‐in‐valve implantation in a degenerated mitral bioprosthesis: A case report and literature review. Issue 6 (24th June 2021) - Perrin, Nils; Müller, Hajo; Noble, Stephane
Abstract: Transseptal TMViV should be considered for mitral bioprosthesis failure especially when large THV can be implanted. Elevated residual mean gradient and its effect on valve durability and potential valve thrombosis remains an unanswered question. Abstract : Transseptal TMViV should be considered for mitral bioprosthesis failure especially when large THV can be implanted. Elevated residual mean gradient and its effect on valve durability and potential valve thrombosis remains an unanswered question.